Beta blockers after myocardial infarction without heart failure: time for a paradigm shift? - Skibicka, Katarzyna; Skibicki, Tomasz; Wesołowska, Weronika; Bujak, Robert (Journal of Education, Health and Sport, 2025)
Background. The role of beta‑blockers (BBs) after myocardial infarction (MI) without heart failure (HF) and with LVEF ≥40% is uncertain in the contemporary era of PCI, dual antiplatelet therapy and high‑intensity statins. Two recent randomized trials - REBOOT‑CNIC and BETAMI-DANBLOCK - provide updated evidence but used different endpoints. Objective. To determine whether BBs confer prognostic benefit after MI in patients without HF and with LVEF ≥40%, to reconcile REBOOT‑CNIC and BETAMI-DANBLOCK with REDUCE‑AMI and ABYSS and to identify subgroups most likely to benefit. Results. REBOOT‑CNIC reported no overall benefit of routine long‑term BB therapy on a hard composite of all‑cause death, recurrent MI, or HF hospitalization. BETAMI–DANBLOCK showed a modest reduction in a broader composite (adding stroke, unplanned revascularization, malignant ventricular arrhythmias, and HF hospitalization), driven mainly by fewer recurrent MIs, with no mortality difference. An individual patient‑data meta‑analysis suggests a benefit signal in patients with LVEF 40–49%, while no clear effect is seen when LVEF ≥50%; REDUCE‑AMI aligns with the latter finding, and ABYSS indicates that abrupt discontinuation may be unsafe. Conclusions. Routine long‑term BB therapy is unlikely to improve prognosis in all post‑MI patients with LVEF ≥50% and no HF. A selective, time‑limited approach appears appropriate, with potential benefit most plausible in LVEF 40–49%; BBs remain valuable for symptom control, and deprescribing should be gradual.